Mapping Readiness for Early IFRS S1 and S2 Adoption among Indonesia’s Carbon-intensive Firms - Andi Nurul Azisah; Eksanti Rahmi Ramadhani (Pattimura Proceeding, 2026)
The strengthening of sustainability and climate-related disclosures has become a global priority following the issuance of IFRS Sustainability Disclosure Standards S1 and S2. However, firms in developing countries continue to face challenges in aligning existing reporting practices with these emerging standards. This study assesses the readiness of carbon-intensive firms in Indonesia for the early adoption of IFRS S1 and S2 through a diagnostic analysis of sustainability disclosures. Using a qualitative content analysis approach, 89 annual and sustainability reports from the energy, chemicals, and construction materials sectors were evaluated based on 29 disclosure indicators across four pillars: governance, strategy, risk management, and metrics and targets. The findings indicate that overall readiness remains low, with relatively higher alignment observed in governance and strategy disclosures, while substantial gaps persist in risk management and, most notably, in metrics and targets. Climate-related quantitative disclosures, particularly those related to emissions measurement, financial impact assessment, and links to accounting assumptions, remain underdeveloped. These results highlight organizational and technical constraints that may hinder effective IFRS S1 and S2 implementation and underscore the need for regulatory guidance and capacity-building initiatives to support IFRS-aligned sustainability reporting in emerging economies